Kajian Karakteristik Preferensi Perjalanan Harian Pengguna Moda Transportasi Pribadi Dan Publik Pada Saat New Normal (Studi Kasus : Kelurahan Paku Jaya - Tangerang Selatan) - Kinasih, Reni Karno; Ridmawan, Adhigma Dite (P3M- Politeknik Negeri Kupang, 2024)
Transportation is an activity of moving something (goods and/or goods) from one place to another, either with or without means. In this context, ownership and use of private and public vehicles can be said to be an alternative for society in meeting movement demands, for example in carrying out daily trips or daily activities and work. However, the pandemic problem used to be one of the causes of the decline in people's daily activities, but now it has started to improve and people's activities are starting to return to normal. This research aims to determine the choice of transportation modes used by the people of Paku Jaya sub-district after the pandemic is over or the new normal and to find out the factors that influence mode users' preferences for daily travel. Data obtained from distributing questionnaires was processed with the help of SPSS software including Chi-Square Test, Cross Tab, and Regression Analysis. It is known that out of 100 respondents, 85 respondents used private vehicles and 15 respondents used public transportation. It is known that variations in gender characteristics, vehicle ownership, and driver's license ownership have significant differences in choosing a mode of transportation. And it is also known that the variables gender, vehicle ownership, and driver's license ownership have a significant influence on mode choice